ANALISIS PENGGUNAAN METODE BERNYANYI DALAM MENINGKATKAN MINAT ANAK TERHADAP LAGU WAJIB NASIONAL - Junila Puteri, Mawaddah; Wulandari, Retno; Fahmi, Fahmi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research aims to increase children's interest in the national compulsory song. The method in this study uses a descriptive qualitative method which uses data triangulation analysis techniques, namely interviews, observation and documentation. The results showed that using the singing method in increasing children's interest in the national compulsory song is very effective, because the singing method is a method that is almost favored by all early childhood, therefore by using the singing method children's interest in the national compulsory song has increased, but there are several factors that can hinder children, namely environmental factors, therefore parents must pay attention to children's environmental factors, because environmental factors are one of the influences on child development.